Etudes amérindiennes : le poids des plumes - Jean-Marc Serme (Amnis)
This paper focuses on Native American cultural initiatives and current debates. Too often, North American Indians have been confined to their tragic history and shown as dependent and helpless. Yet Native American intellectuals and militants have been engaged in cultural re-definition in the last forty years. The paper will draw extensively from two recent collections of essays: Susan Lobo & Steve Talbot, eds. Native American Voices: A Reader. New York: Longman, 1998; Duane Champagne, ed. Contemporary Native American Cultural Issues. Walnut Creek: AltaMira Press, 1999. The subject is highly sensitive and political, therefore I will be careful to give both a faithful account of the authors’ views without ignoring the political context of the dominant society.